2008
DOI: 10.1021/ja804021m
|View full text |Cite
|
Sign up to set email alerts
|

Bis-Sulfonyl Ethylene as Masked Acetylene Equivalent in Catalytic Asymmetric [3 + 2] Cycloaddition of Azomethine Ylides

Abstract: Enantioenriched 3-pyrrolines have been synthesized by highly enantioselective Fesulphos-Cu-catalyzed 1,3-dipolar cycloaddition of azomethine ylides with trans-1,2-bisphenylsulfonyl ethylene, followed by reductive sulfonyl elimination. High levels of reactivity, exoselectivity, and enantioselectivity have been accomplished for a variety of substituted azomethine ylides. This cycloaddition-desulfonylation strategy has been applied as a key step in the enantioselective synthesis of a biologically active C-azanucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(35 citation statements)
references
References 30 publications
(11 reference statements)
2
33
0
Order By: Relevance
“…As masked acetylene equivalent, disulfone 11 has been used in this 1,3-DC for the preparation of very interesting Schramm's C-azanucleoside, 15 which is a promising trypanosomal nucleoside hydrolase inhibitor. In this work the enantioselective synthesis of the exo-cycloadduct (type 12) was the key step of the total process, and next the methoxycarbonyl group was reduced with lithium aluminum hydride (LAH) followed by the complete desulfonylation with sodium amalgam.…”
Section: Applications Of (S a )-Binap-agx Catalyzed 13-dcmentioning
confidence: 99%
“…As masked acetylene equivalent, disulfone 11 has been used in this 1,3-DC for the preparation of very interesting Schramm's C-azanucleoside, 15 which is a promising trypanosomal nucleoside hydrolase inhibitor. In this work the enantioselective synthesis of the exo-cycloadduct (type 12) was the key step of the total process, and next the methoxycarbonyl group was reduced with lithium aluminum hydride (LAH) followed by the complete desulfonylation with sodium amalgam.…”
Section: Applications Of (S a )-Binap-agx Catalyzed 13-dcmentioning
confidence: 99%
“…[11] However, under these reaction conditions [[Cu(CH 3 CN) 4 ]PF 6 (10 mol %), fesulphos ligand (3; 10 mol %), and Et 3 N (18 mol %) in CH 2 Cl 2 at room temperature] we observed the formation of a complex mixture of isomers. [14] In an attempt to improve the selectivity of the cycloaddition we next turned to using the diastereoisomeric dipolarophile, methyl (Z)-3-phenylsulfonylpropenoate (2).…”
mentioning
confidence: 93%
“…This type of structural unit is frequently found in natural, and biologically active compounds. For instance, 2,3-dicarboxylic acid substituted pyrrolidine units are potent and selective inhibitors of glutamate receptors and glutamate transporters, [7] and they have been used in the design of new peptides and constrained peptidomimetics.[8] Taking into account that most methods currently used in the preparation of pyrrolidines with 2,3-dicarboxylic acid substitution are based on multistep approaches from a-amino acid precursors, [9] the development of more convergent synthetic strategies is highly desirable.We have recently reported that unsubstituted vinyl sulfones [10] and bis(sulfonyl)ethylenes [11] are excellent dipolarophiles in the catalytic asymmetric 1,3-dipolar cycloaddition of azomethine ylides. Bearing in mind the excellent properties of the sulfonyl group both as a powerful electronwithdrawing group and as an easily removed substituent, [12] we envisaged that the regioselectivity of the catalytic asymmetric reaction of sulfonyl acrylates with azomethine ylides derived from iminoesters could be controlled by the sulfonyl moiety rather than the ester group, [13] and lead to the regioselective and stereoselective formation of 2,3-dicarboxylic acid substituted pyrrolidines (Scheme 1).…”
mentioning
confidence: 99%
“…[27] We had previously described that 6 ] was a very effective catalyst in the asymmetric 1,3-dipolar cycloaddition of 2 with the azomethine ylides of a-iminoesters in the presence of chiral 2-(tert-butyl-sulfenyl)-1-(diphenylphosphino)ferrocene (FeSulPhos) ligands. [28] Thus, for the nonenantioselective version of this process we chose similar reaction conditions but by using PPh 3 as ligand: [Cu- 6 ] (3 mol %), PPh 3 (3 mol %), and Et 3 N (18 mol %). In the model reaction between N-benzylidene glycine methyl ester (1 a) and 2, complete conversion was observed after 5 h and a single bisA C H T U N G T R E N N U N G (sulfonyl) adduct, 5 a, was isolated by standard silica-gel chromatography.…”
Section: Resultsmentioning
confidence: 99%